ANALISIS KELIMPAHAN DINOFLAGELLATA BENTIK PADA SUBSTRAT BUATAN DI PERAIRAN KOTA PADANG SUMATERA BARAT - Tengku Mutia Smita Dwivayana; Thamrin Thamrin; Efriyeldi Efriyeldi (Program Pascasarjana Universitas Riau, 2015)
ABSTRACTDinoflagellates are group of phytoplankton that is besides plankton are also benthic. Its abundance in the waters may cause red tide phenomenon. Abundance of Benthic Dinoflagellates in waters influenced by several environtmental factors. The method used is an experimental method. Sampling using artificial substrates (gauze). The results showed on the Muara Padang station has the highest concentration of nitrate and phosphate are 0,195 and 0,028 mg/l with the lowest value of the abundance of benthic Dinoflagellates 400,4 cells/100cm2 and the lowest concentration of nitrate and phosphate is located on the Teluk Bungus station are 0,033 and0,003 mg/l with the highest value of the abundance of benthic Dinoflagellates 660,4 cells/100cm2.